2019
DOI: 10.1051/parasite/2019053
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variations in wing morphology of Aedes albopictus (Diptera, Culicidae) in Albania, the region where it was first recorded in Europe

Abstract: The rapid spread and settlement of Aedes albopictus mosquitoes across at least 28 countries in Europe, as well as several countries in Asia Minor, the Middle East and Africa, has made it one of the most invasive species of all time. Even though the biology of Ae. albopictus in its native tropical environment has been documented for a long time, the biology and ecology of this species in newly colonized temperate environments remain poorly known despite its important role as a vector for about twenty arboviruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Together, the results of this study demonstrate that landmark-based wing morphometry analysis could be an alternative tool for identifying mosquito species in Thailand, consistent with the findings of previous studies on three epidemiologically important genera ( Anopheles , Aedes , and Culex ) [ 15 , 17 , 23 ] and Mansonia [ 49 ]. However, this study utilized a limited number of Ae .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Together, the results of this study demonstrate that landmark-based wing morphometry analysis could be an alternative tool for identifying mosquito species in Thailand, consistent with the findings of previous studies on three epidemiologically important genera ( Anopheles , Aedes , and Culex ) [ 15 , 17 , 23 ] and Mansonia [ 49 ]. However, this study utilized a limited number of Ae .…”
Section: Discussionsupporting
confidence: 90%
“…GM has been applied extensively in a number of fields, including entomology, where it has been used to analyze blow flies, mosquitoes, bees, and Triatominae eggs [ 14 ]. In addition, several recent studies have used GM to classify species and examine variation among clinically important mosquitoes that are morphologically similar or are sibling species [ 15 17 ]. Currently, GM based on the geometry of wing features (landmark-based) is largely used in medical entomology to reliably distinguish between closely related species [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study conducted in Albania on Ae. albopictus has revealed that low temperatures reduce mosquito development rates resulting in large bodied mosquitoes with increased wing sizes specially among females (Prudhomme et al, 2019) slowing their movement at high altitudinal areas. Aytekin et al (2009) also described that at low temperatures, Anopheles superpictus show longer egg incubation periods and low larval survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in Culex theileri , a positive correlation was observed between wing size and altitude [ 18 , 32 ]. Recently, in Aedes albopictus of Albania, the region where this Asian mosquito was first registered in Europe, it was observed between 154 and 1,559 m shape, size and sex variations among altitudinal populations of these species [ 33 ]. Nevertheless, in Colombia and the rest of the world, the metric variation of A .…”
Section: Introductionmentioning
confidence: 99%